Health consequences of shift work and insufficient sleep. (1st November 2016) - Kecklund, Göran; Axelsson, John
Abstract : This review summarises the literature on shift work and its relation to insufficient sleep, chronic diseases, and accidents. It is based on 38 meta-analyses and 24 systematic reviews, with additional narrative reviews and articles used for outlining possible mechanisms by which shift work may cause accidents and adverse health. Evidence shows that the effect of shift work on sleep mainly concerns acute sleep loss in connection with night shifts and early morning shifts. A link also exists between shift work and accidents, type 2 diabetes (relative risk range 1.09-1.40), weight gain, coronary heart disease (relative risk 1.23), stroke (relative risk 1.05), and cancer (relative risk range 1.01-1.32), although the original studies showed mixed results. The relations of shift work to cardiometabolic diseases and accidents mimic those with insufficient sleep. Laboratory studies indicate that cardiometabolic stress and cognitive impairments are increased by shift work, as well as by sleep loss. Given that the health and safety consequences of shift work and insufficient sleep are very similar, they are likely to share common mechanisms. However, additional research is needed to determine whether insufficient sleep is a causal pathway for the adverse health effects associated with shift work.